Corrosion Localization Analysis in T-Shape Pipe Junction Based on Multielectrode Current Measurements - Georgii S. Vasyliev (Advances in Materials Science and Engineering)
The water flow rate and galvanic current distribution in the T-shape junction of steel pipes were investigated using the multielectrode array approach. The inner surface of polypropylene pipes junction was divided into 15 separate sections, and a steel plate was placed in every section to form a single inner surface. The tap water flow rate varied between 0.28 and 0.57 m/s, and the water distribution in the junction was between 5 : 1 and 1 : 5. The galvanic current flowing through each steel electrode was mapped on the 3D model of the T-shape junction. Two differential aeration pairs were found with high anodic current densities.